The optimal placement of phasor measurement units and their effects on state estimation - Yuill, William (Department of Electrical Engineering, 2014)
Phasor measurement units (PMUs) are a key new technology for use in electric power systems as a backbone for sensing and measurement and to improve interface and decision support using instantaneous PMU data which will drive faster simulations and advanced visualisation tools that will help system operators assess dynamic challenges to system stability. The two main objectives of this work are to investigate and develop 1. a method for the algorithmic placement of a minimum number of PMUs into a system to ensure full observability, 2. conventional, hybrid and linear state estimation techniques to incorporate and utilize PMU measurement data to perform state estimation and to study the effects that differing PMU placement positions have on the accuracy of the resultant state estimator solution.